Keragaman Morfologi dan Genetik Beberapa Aksesi Tanaman Sagu (Metroxylon Sagu Rottb.) Berdasarkan Penanda Molekuler Gen Mat-K - Eka Fitri Wulandari; Nouke Lenda Mawikere; Barahima Abbas (Cassowary, 2021)
Sago palm (Metroxylon sago Rottb.) is one of the carbohydrate-producing crops that has great potential in supporting food security programs. This study aims to determine the morphological and genetic diversity based on the mat-K gene marker of 15 accessions of sago pal that have been collected by the Sago Research Consortium. This research was conducted by preparing plant samples, extracting DNA, amplifying DNA with a PCR tools, visualizing the results of DNA amplification, sequencing, editing DNA sequencing, and blasting. The results showed that the sago palm accessions collected by the UNIPA Sago Research Consortium were morphologically different in the Russet stages. Based on the maturase K (mat-K) gene marker of 15 sago palm accessions were divided into two haplotypes, namely haplotype 1 which experienced deletion at base number 5 (amino acid phenylalanine) and haplotype 2 which did not experience deletion so it had phenylalanine amino acid. Phylogenetic analysis showed that 15 sago palm accessions were divided into 2 groups, namely group 1 and group 2. Sago palm were observed closely related to Metroxylon warburgii with genetic distance of 0.001.